Discipline and liberty - "Palmer, Gareth" (New York, 2003)
This study is about the different ways in which television represents the public, and how television recommends we conduct ourselves in all spheres of our lives. Taking Foucault's notion of governance - the conduct of conduct - Gareth Palmer applies it to a range of television formats which have loosely been described as "reality TV". The relatively older form of documentary production, with its set of established practices addressing a certain form of citizen who had few channels to choose from, has been transmogrified. The new production climate has spawned a huge range of choices as the programmes have dizzyingly different approaches, intentions and aspirations. These hybrid formats - "Big Brother", "Video Diaries", "Judge TV", "Rikki Lake" and "Stupid Behaviour Caught on Tape" - use a technology of discipline to produce confessions, revelations and transformations which render citizens more transparent than ever and can punish those of us who dare to be different. Looking at how various agencies of the state have exhorted us to report crime - license fee and tax evasion, street crime, even benefit fraud - the author shows how constant surveillance has come to equal good citizenship. The book should be of use to anyone interested in television, television documentary, programme production, media studies, sociology and politics.
Keywords: Societies